Combination of T-DM1 and platinum-based chemotherapy in patient-derived xenograft models of muscle-invasive bladder cancer - Abolfazl Razzaghdoust; Samad Muhammadnejad; Mahmoud Parvin; Bahram Mofid; Masoumeh Zangeneh; Abbas Basiri (Iranian Journal of Basic Medical Sciences, 2022)
Objective(s): To assess the efficacy and safety of T-DM1, as an anti-HER2 antibody-drug conjugate (ADC), alone and in combination with two platinum-based chemotherapy regimens in patient-derived xenografts (PDXs) of muscle-invasive bladder cancer (MIBC) established in immunodeficient mice. Materials and Methods: After treatment initiation, tumor size was measured twice a week. Percent of tumor growth inhibition (TGI) and tumor response rates were calculated as efficacy endpoints. To evaluate treatment toxicity, relative body weight (RBW) was calculated for each group. For comparison of TGIs between treatment groups, the Kruskal-Wallis test was used. Also, the significance of the overall response (OR) rate between placebo groups with treatment groups was analyzed using Fisher’s exact test. Immunohistochemistry and fluorescence in situ hybridization techniques were used to evaluate the level of HER2 expression.Results: Our data showed that T-DM1 alone induced a moderate antitumor activity. While chemotherapy regimens induced a slight TGI when administered alone, interestingly, they showed strong antitumor activity when administered combined with T-DM1. The OR rates were higher when T-DM1 was combined with chemotherapy regimens than T-DM1 alone. When compared with the placebo group, the OR rates of combination groups were statistically significant. Our data also showed that the administered dose of each drug was well tolerated in mice. Conclusion: The combination of T-DM1 and platinum-based chemotherapy may represent a new treatment option for bladder tumors with even low HER2 expression, and could also provide substantial novel insight into tackling the challenges of MIBC management.